Factors Associated with Diet Compliance with Hypertension Patients - Fitriyanti Patarru'; Mery Solon; Graciela Talebong; Hana Rannu (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Hypertension or high blood pressure is a condition in which a person experiences an increase in blood pressure above normal for a long period. One of the efforts to prevent hypertension is to adhere to the recommended diet. There are several factors related to dietary compliance in patients with hypertension, two of which are family support and education level. Objectives: The purpose of this study was to determine the relationship between family support and education level with dietary compliance in patients with hypertension. Methods: This type of research is a quantitative study with an analytical observational design using a cross-sectional approach. Sampling in this study uses non-probability sampling with a total sampling approach and data collection using a questionnaire. This research was conducted in February 2022. Results: The results of statistical tests using the chi-square test showed that the results for the family support factor were p = 0.001, and the results for the education level factor were p = 0.001. It can be concluded that there is a relationship between family support and education level with dietary compliance in patients with hypertension. Conclusion: Factors related to hypertension diet compliance are factors of knowledge, family support, motivation, and desire from within to recover.